Effects of humate and neodymium on phytochemical levels in kale at different ontogenetic stages - J. D. Anteh; O. A. Timofeeva; A. A. Mostyakova (Regulatory Mechanisms in Biosystems, 2021)
The increased global mortality caused by the rise in chronic diseases can be reduced by the consumption of antioxidant-rich foods. Leafy green kale (Brassica oleracea var. sabellica) has high nutritional value due to its high antioxidant content and its consumption is highly correlated with a reduced risk of developing some chronic diseases. The paper focuses on examining the effects of two different mineral nutrients – neodymium and potassium humate – on the accumulation of flavonoids, vitamin C, phenolic compounds, carotenoids and malondialdehyde (MDA) content in field-grown leafy green kale. Leaves from treated plants were collected at three stages of maturity –14 weeks, 18 weeks, and 22 weeks and subjected to spectrophotometric analysis. The results showed that the stimulatory effect of both mineral nutrients on the phytochemicals varied at the different growth stages - the highest significant effect of neodymium has been mostly observed at week 18 with high flavonoid, vitamin C, and carotenoid levels. Phenolic compounds for this variant are the same as in the control samples, while the level of malondialdehyde was reduced by 21.8%, signifying increased antioxidant activity. The rare earth element primarily maintained some phytochemical content at weeks 14 and 22. Following soil treatment with potassium humate, the levels of studied phytochemical compounds were either maintained or elevated at weeks 14, 18, and 22. Humic acid exerted the greatest decrease in malondialdehyde content in kale at week 14, indicating a reduction in the lipid peroxidation process in leaves. Accordingly, the harvest date of leafy green kale (Brassica oleracea var. sabellica) should depend on the type of mineral nutrient applied. The obtained results provide information that may be relevant to the production of functional varieties and enhance the nutritional and possibly the economic value of kale.